2014
DOI: 10.5535/arm.2014.38.2.167
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Effects of Suprascapular Nerve Block, Intra-articular Steroid Injection, and a Combination Therapy on Hemiplegic Shoulder Pain: Pilot Study

Abstract: ObjectiveTo assess the relative effectiveness of three injections methods suprascapular nerve block (SSNB) alone, intra-articular steroid injection (IAI) alone, or both-on relief of hemiplegic shoulder pain.MethodsWe recruited 30 patients with hemiplegic shoulder pain after stroke. SSNB was performed in 10 patients, IAI in 10 patients, and a combination of two injections in 10 patients. All were ultrasonography guided. Each patient's maximum passive range of motion (ROM) in the shoulder was measured, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Subacromial injection with corticosteroid is known to improve pain and function in non-stroke patients with rotator cuff disorder. Jeon et al 18 ) reported that US-guided suprascapular nerve block, intra-articular steroid injection, and a combination therapy on HSP significantly improved shoulder ROM and pain with time, but no statistically significant difference was found between them. Suprascapular nerve block is a safe and efficacious treatment of HSP 36 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subacromial injection with corticosteroid is known to improve pain and function in non-stroke patients with rotator cuff disorder. Jeon et al 18 ) reported that US-guided suprascapular nerve block, intra-articular steroid injection, and a combination therapy on HSP significantly improved shoulder ROM and pain with time, but no statistically significant difference was found between them. Suprascapular nerve block is a safe and efficacious treatment of HSP 36 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound (US)-guided injections are widely used because of the advances in image quality, decreased cost of use, portability and lack of radiation exposure 16 ) . Recently US-guided injections showed greater accuracy than landmark technology for all shoulder pain treatment, with the exception of the target space 17 , 18 , 19 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Jeon et al [5] compared the effects of intra-articular steroid injection, SSNB and combined administration of both approaches in patients with HSP. They reported that all the injection regimens, which were performed under USG guidance, had similar beneficial effect in the management of poststroke patients with shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In order to relieve pain; various treatment modalities such as physical therapies, functional electrical stimulation, oral or intra-articular steroid injections, stellate ganglion block and peripheral nerve blocks have been used. [5] Recently, suprascapular nerve block (SSNB) has been commonly preferred for the treatment of shoulder disorders. The suprascapular nerve supplies 70% of sensorial fibers to the shoulder.…”
mentioning
confidence: 99%
“…This technique has previously been demonstrated to be safe, and it effectively blocks the articular branches of the suprascapular nerve [63]. For treatment of chronic shoulder conditions, injectable steroids usually are added to the local anaesthetic solution (10 ml solution of 0.5% bupivacaine hydrochloride and 40 mg of methyl prednisolone acetate) [65][66][67][68][69][70]. Local steroid injection blocks transmission through nociceptive C fibers, thus prolonging the effect of the local anaesthetic through alteration of the function of K channel on the excitable tissue [71,72].…”
Section: Dangoisse Techniquementioning
confidence: 99%